Effects of osmolytes on solvent features of water in aqueous solutions. Issue 5 (4th April 2017) - Ferreira, Luisa A.; Breydo, Leonid; Reichardt, Christian; Uversky, Vladimir N.; Zaslavsky, Boris Y.
Abstract : The solvatochromic solvent features of water (dipolarity/polarizability, π *, hydrogen bond donor acidity, α, and hydrogen bond acceptor basicity, β ) of water have been determined in aqueous solutions of erythritol, glucose, inositol, sarcosine, xylitol and urea with concentrations from 0 to 3 M and higher. The concentration effects of the osmolytes on the solvent features of water were characterized and compared with those reported previously for sorbitol, sucrose, trimethylamine N-oxide (TMAO), and trehalose. The solvent features of water in solutions of all osmolytes except TMAO and sarcosine were established to be linearly interrelated. It is shown that the concentration effects of essentially all nonionic osmolytes depend on osmolytes' lipophilicity, molecular polarizability, and polar surface area. It is demonstrated that solubility of various compounds in aqueous solutions of glucose, sucrose, sorbitol, and urea of varied concentrations may be described in terms of solvent dipolarity/polarizability of water in these solutions. Surface tension of aqueous solutions of sucrose and sorbitol may also be described in the same terms. The relative permittivity of aqueous solutions of glucose and sucrose may be described in terms of the solvent hydrogen bond donor acidity of water. It is suggested that the effects of nonionic osmolytes on behavior of proteins and nucleic acids in aqueous media may be considered in terms of the altered solvent features of water instead of "nano-molecular crowding" effect.